Analysis of tumour control probability, normal tissue complication probability and isotoxic effects for prostate cancer - Fauzee, Nurnada Syahrain Mohd (Universiti Sains Malaysia, 2016)
The purpose of this study is to analyse the Tumour Control Probability (TCP), Normal Tissue Complication Probability (NTCP) and isotoxic effect for prostate cancer. Eight prostate treatment plans with Collapsed Cone algorithm were evaluated in term of TCP, NTCP and isotoxic effect using BioSuite and BIOPLAN software. The treatment plans were then recalculated using Pencil Beam algorithm and similar TCP, NTCP and isotoxic effects were evaluated. Evaluation of all the treatment planning were conducted based on the DVH data from Oncentra MasterPlan (OMP) transferred to the both software. The results indicate that NTCP value of rectum is higher for LKB model while for bladder; the value is higher using RS model. For all plans, the TCP values are 100% and isotoxic effect of organs are below the isotoxic level (5%). Pencil Beam shows a slightly higher than Collapsed Cone in total dose of target volume for most of plans. NTCP value obtained from BIOPLAN is greater than NTCP value from BioSuite. Total dose calculation of target volume for DVH from OMP is varied from BioSuite. In summary, there is no significant different between Pencil Beam and Collapsed Cone algorithm in TCP, NTCP and isotoxic effects. The dissimilarity in dose calculation using different algorithm is influenced by anatomical position of organ, tumour volume and treatment planning system. Variation in evaluation method will not give similar findings even same data is used. Software development between BioSuite and BIOPLAN indicates a larger difference in NTCP values between two different softwares.